Arabic Speaking Learning through Synchronous and Asynchronous Approaches - Anisatu Thoyyibah; Achmad Tito Rusady (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2022)
The purpose of this study was to this study aimed to describe the learning of Arabic speaking skill or maharah al-kalam (Kalam 1) through synchronous and asynchronous approaches in the pandemic era in terms of the process, media, evaluation, problems, and challenges in the Arabic Education Department, with a qualitative research approach. The approach in this study used descriptive qualitative with the type of research conducted in the form of case studies. Collecting data used were observation, interview, and documentation techniques. Analysis of the data used Miles, Huberman, and Saldana through the stages of data collection, data condensation, data display, and conclusion/verification. While the results obtained were the learning process using synchronous learning and asynchronous learning. The media used varies according to needs. Evaluation is in the form of oral and video recording. The problems experienced in the form of linguistic and non-linguistic, as well as challenges faced by academic and non-academic factors.